Dynamics of the Morphological Changes in the Progo River Due to Lahar Transport from Merapi Volcano - Adhitama, Adib Prima; Jatmiko, Retnadi Heru; Mei, Estuning Tyas Wulan; Sartohadi, Junun (Indonesian Journal of Geography, 2024)
The Merapi eruption in 2010 and 1975 caused lahar floods on the Progo River segment in Kulon Progo. This study aims to analyze the dynamics of river morphology changes that are affected by two lahar floods. Temporal images representing the two lahar flood events up to several years later were used to see river morphology changes. Temporal data from remote sensing and UAV is able to indicate the morphological change of river valleys in the study area. The analysis was carried out based on the parameters of river slope, riverbank morphology, and river curvature. The river slope is 0.74% which means the slope is flat. This condition gives a consequence of the river's meandering morphology. The morphology of the riverbank has the "U" shape, providing more surface area for river water to drain. The sinuosity ratio (SR) is dynamic during two lahar flood periods. In the 2010 lahar flood period, the SR pre-lahar flood was 1.92, increased significantly to 2.65 eight months post-lahar flood, and decreased significantly to 1.60 one year later. Lahar floods are the main factor causing these dynamics in this period. The annual SR for the next ten years is always changing but the fluctuations are more stable and tend to decrease. The SR's fluctuations in this period provide evidence that the river morphology is always changing even without major triggers. In the 1975 lahar flood period, the SR value was known from the PBB maps three years pre-events, five years post-events, and Google Earth images ten years post-events. The SR in this period fluctuated, and the meander became simpler at ten years post-events. The results of this paper provide evidence that spatial analysis with temporal images is more efficient and economical for studying river morphological dynamics.